Physical parameter testing on the CARRAGEENAN of KAPPAPHYCUS STRIATUM enhanced with different fertilizers. - Chan, Angela (UPHSI, 2009)
Quality of carrageenan from seaweeds deteriorates. Physical parameter testing was done on the carrageenan of Kappaphycus striatum enhanced with different fertilizers. There were four treatments namely Treatments A, B, C, and D. Treatment A contains 16-20-0 Commercial fertilizer. Treatment B 14-14-14 contains Commercial fertilizer. Treatment C contains Modified Grund Medium (MGM) Fertilizer. Treatment D is the treatment with no fertilizer applied; this served as the control treatment. Physical parameters were observed to test the carrageenan quality of K. striatum ehanced with treatments. The Physical Parameters were of the following: Percent Yield, Gel Strength, Gelling Temperature, and Melting Temperature. Carrageenan with MGM (Modified Grund Medium) fertilizer gave the highest percent yield of 10%, while the treatment no fertilizer gave the least percent yield of 7%. 16-20-0 showed the lowest gel strength of 368.74 g/cm^2 while the treatment no fertilizer gives the higest gel strength of 819.3 g/cm^2. Treatment, no fertilizer shows the lowest melting temperature of 82.67 degrees celcius while the MGM shows the higest melting temperature of 93.167 degrees celcius. 14-14-14 shows the lowest Gelling Temperature of 70.67 degrees celcius while the MGM shows the higest gelling temperature of 74.67 degrees celcius. Overall, MGM is the best fetilizer that can enhance the quality of the carrageenan in our study.